PENGARUH ANTARA TATA KELOLA PERUSAHAAN (CORPORATE GOVERNANCE) DENGAN STRUKTUR MODAL PERUSAHAAN - Kurniawan, Vito Janitra; Nur Rahardjo, Shiddiq (Diponegoro Journal of Accounting, 2014)
The purpose of this research was to determine the effect of corporate governance with the company's capital structure . To obtain that capital is usually the company issuing new shares or by borrowing from creditors. Error in determining the capital structure will have a broad impact for the company . The decision could lead to the addition of the company's capital so necessary to the agency problem of corporate governance mechanisms . Board size , managerial ownership , institutional ownership and audit committee is part of corporate governance used in this study .This research was conducted by the method of documentation of the annual report companies listed in Indonesia Stock Exchange ( IDX ) 2010-2012 . The sampling method used in this study was purposive sampling , the number of samples obtained 195 samples . Testing hypotheses using regression analysis . The results of this study showed variable managerial ownership and audit committee has significant and negative effect on the capital structure . While variable board size has a positive effect but no significant effect on capital structure . So also with institutional ownership shows negative and significant relationship to the capital structure .